The Impact of Traumatic Stress, Resilience, and Threats to Core Values on Nurses During a Pandemic. (October 2022) - Swavely, Deborah; Romig, Barbara; Weissinger, Guy; Holtz, Heidi; Alderfer, Mary; Lynn, Lisa; Adil, Thomas; Rushton, Cynda Hylton
Abstract : OBJECTIVE: The aim of this study was to understand the traumatic stress and resilience of nurses who cared for patients with COVID-19. BACKGROUND: Studies have shown a high proportion of healthcare workers are at risk for developing posttraumatic stress disorder after a pandemic. Resilience factors are believed to play an important role in the well-being of healthcare professionals. METHODS: This was a triangulated mixed methods study; a phenomenological qualitative approach with survey data was used to triangulate the findings, and sensemaking was used as the theoretical framework. RESULTS: Four themes emerged from the study: 1) phases of traumatic stress response to perceived threats; 2) honoring their sacrifice; 3) professional self-identity; and 4) sustaining resilience in a stressful work environment. Quantitative results on traumatic stress, general resilience, and moral resilience supported the themes. CONCLUSIONS: The findings will help leaders understand the potential for postpandemic mental health problems and the role of resilience in maintaining well-being.